Reconstructing diet at the Neolithic stalled cairn of the Knowe of Rowiegar, Rousay, Orkney, using stable isotope analysis. (June 2017) - Gigleux, Ciara; Richards, Michael P.; Curtis, Neil; Hutchison, Margaret; Britton, Kate
Abstract: In this study, human remains from the Neolithic stalled cairn of the Knowe of Rowiegar, Rousay, Orkney (3620–2880 cal BC, 95.4% probability), were analysed for bone collagen stable carbon ( δ 13 C) and nitrogen ( δ 15 N) isotope ratios in order to determine the dietary adaptations of individuals buried at the site, particularly the contribution of marine protein in the diet. Collagen was extracted from bone from 13 individuals (11 males, 1 female, and 1 sub-adult), and stable isotope data generated were compared with previously-published Neolithic Orcadian faunal data, and with human and animal bone collagen isotope data from other published British Neolithic sites. The results from the Knowe of Rowiegar suggest that the dietary protein of those buried at the site was largely terrestrial in origin, which is similar to other British Neolithic bone collagen datasets, albeit with the possible minor inclusion of marine protein. Intra-group comparison highlights the potentially different dietary habits of the single female and sub-adult individuals sampled from the site compared to the interred males. Geographical variations in both humans and animals (particularly in nitrogen isotope ratios) across Britain are examined, and the consumption of marine fish and the influence of herbivore baseline variability in the study of Neolithic human diet are explored. Highlights: Bone collagen was extracted from Orcadian Neolithic skeletons to investigate palaeodiet. δ 13 C and δ 15 N values suggest diet dominated by terrestrial sources, albeit with possible minor marine contribution Intra-group comparisons suggest some dietary variability between individuals. Δ-values (mean human-herbivore) further evidence minor marine dietary contribution at Rowiegar and other Northern Isles sites. Emerging regional variability in isotope values across Neolithic Britain is discussed.